2007
DOI: 10.1016/j.nlm.2007.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenesis and learning: Acquisition and asymptotic performance predict how many new cells survive in the hippocampus

Abstract: Previous research has shown that some associative learning tasks prevent the death of new neurons in the adult hippocampus. However, it is unclear whether it is mere exposure to the training stimuli that rescues neurons or whether successful learning of the task is required for enhanced neuronal survival. If learning is the important variable, then animals that learn better given the same amount of training should retain more of the new cells after learning than animals that do not learn as well.Here we examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
60
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 29 publications
(43 reference statements)
3
60
0
2
Order By: Relevance
“…Nevertheless, the correlation between performance and cell survival was evident in the first experiment when neurons were <2 wk of age, and again in the second experiment, when neurons were mature at nearly 4 wk of age. The data presented here are consistent with a recent report in which individual differences in learning related to the number of cells that survive after training (Dalla et al 2007). In that study, animals were exposed to either trace eyeblink conditioning or contiguous trace conditioning.…”
Section: Cold Spring Harbor Laboratory Press On May 11 2018 -Publishsupporting
confidence: 92%
“…Nevertheless, the correlation between performance and cell survival was evident in the first experiment when neurons were <2 wk of age, and again in the second experiment, when neurons were mature at nearly 4 wk of age. The data presented here are consistent with a recent report in which individual differences in learning related to the number of cells that survive after training (Dalla et al 2007). In that study, animals were exposed to either trace eyeblink conditioning or contiguous trace conditioning.…”
Section: Cold Spring Harbor Laboratory Press On May 11 2018 -Publishsupporting
confidence: 92%
“…In previous studies, the increase in cell survival after training was preferentially expressed in animals that learned, defined as those animals that expressed CRs on at least 60% of the trials in a session. The increase in survival did not occur in animals that were exposed to the same number of trials but did not learn to express the CR (8). In the present study, we replicated this finding and extend it to include females; the number of surviving cells was elevated in animals emitting CRs on at least 60% of the trials within a session (n ϭ 7 males and n ϭ 7 females) (F (1,27) ϭ 7.4, P ϭ 0.01) ( Fig.…”
Section: Females Outperform Males During Training With Trace Eyeblinkmentioning
confidence: 89%
“…Adult neurogenesis in the rat hippocampus is affected by learning and is perhaps involved in related processes (3)(4)(5)(6)(7). Specifically, it has been shown that learning a new task enhances the survival of the new cells that were generated in the dentate gyrus (DG) of the hippocampus 1 week before the training began (8)(9)(10)(11)(12)(13), while it has no effect on other neurogenic regions, such as the subventricular zone (11). The vast majority of these surviving cells differentiate into neurons and many are incorporated into the circuitry of the hippocampus (7,12,14,15).…”
mentioning
confidence: 99%
See 2 more Smart Citations